Peningkatan Pengetahuan Ibu Tentang Gizi Seimbang Pada Balita - Kusmiati, Meti; Khaidiza Dhiazahra, Diffa; Novianti, Puput; Erliza R.F, Raden; Ariyani, Syafitri; Althafah, Zahra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Balanced nutrition is daily food intake whose types and amounts of nutrients are in accordance with the body's needs. Fulfillment of nutrients obtained from daily food must pay attention to the principles of food diversity, physical activity, clean living behavior, and maintaining a normal body weight to prevent nutritional problems. To increase the knowledge of mothers under five regarding balanced nutrition, especially mothers under five in RW 02 Sirnagalih Village. This activity was carried out using a sampling method by sampling 25 respondents to obtain research results, so in this study used T test analysis in the pre test and post test with a p value <0.05. The results of statistical test calculations using a computerized system, namely using the SPSS application, obtained a value of t = -3.361 and p = 0.003 (p<0.05). The research results showed that respondents' knowledge increased after completing the counseling compared to before the counseling. The results obtained were 40% knowing about balanced nutrition then it became 72% after counseling. From community service activities in the field of theory/material delivery the results are quite good and acceptable. The results of this research can be concluded to provide health education to increase the knowledge of mothers of toddlers regarding balanced nutrition in RW 02 Sirnagalih Village.